PEMANFAATAN TEKNOLOGI LUBANG BIOPORI SEBAGAI PEMBUATAN PUPUK KOMPOS DI KELURAHAN TANGKERANG LABUAI KOTA PEKANBARU - Siti Juariah; Susi Endrini; Wili Octovia Lastari; Desy Ameiliani; Niki Nuriasih Sasmita Ningrum; Ailsa Islami; Selvia Rahmayani; Hanifa Zulfa; Regi Agusti Pratama; Viny Sofy Saputri (LPPM Universitas Andalas, 2023)
The issues in the environment continue to evolve and become increasingly complex. Urban areas in Indonesia still face problems in waste management. Food waste in Riau constitutes 45.1%, and in Pekanbaru alone, it accounts for 59%. People tend to perceive that once they dispose of their waste outside, it's no longer their concern. This lack of concern leads to an increasing and uncontrollable amount of waste. This initiative aims to reduce waste and prevent environmental flooding. The creation of biopores took place on August 23, 2023, located in Tangkerang Labuai Village, RW 03, Bukitraya Subdistrict. The activity was a collaboration between students from Abdurrab University, Group 5, and Mr. Mirshal (a resident of RW 003). The outcome of this activity was the utilization of biopores as organic waste composting sites, producing quality liquid compost. The use of Biopores is also intended as a water resource for reducing excessive water stagnation. Biopores are holes in the ground formed by various soil organisms such as earthworms, plant roots, termites, and other soil creatures. They aid in flood prevention and groundwater reserve enhancement. Utilizing Biopores as water reservoirs helps mitigate household organic waste, contributing to flood control and even improving soil fertility.